The Therapeutic Potential of Inflamed Gingiva-Derived Mesenchymal Stem Cells in Preclinical Studies: A Scoping Review of a Unique Biomedical Waste - Gamilah Al-Qadhi; Sarah Al-Rai; Layla Hafed (Stem Cells International)
Searching for considerable abundance, simple, and accessible sources in stem cell-based therapy opens the door for isolation of a new population of oral/dental stem cells known as inflamed gingiva-derived mesenchymal stem cells, which have recently come to light with promising therapeutic potential in tissue regenerative therapy. Following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidelines, this scoping review is aimed at highlighting the possible therapeutic potential of inflamed gingiva-derived mesenchymal stem cells in preclinical studies carried out to date and presenting the current evidence depends upon their comparison to the healthy gingiva-derived mesenchymal stem cells or other mesenchymal stem cell sources. A comprehensive electronic search using (PubMed, Embase, Scopus, and Web of Science) databases and a manual search of relevant references were conducted until June 2020. Included studies were assessed using a combination tool, including the guidelines for reporting preclinical in vitro studies on dental materials, which were based on the modification of the Consolidated Standards of Reporting Trial checklist and the guidelines for animal research: reporting of in vivo experiments. The initial research provided 360 articles, with 13 articles that met the inclusion criteria. While most of the included studies lacked randomization, blinding, and sample size calculation, they were designed accurately in other aspects of the guidelines. The results of this scoping review indicated that inflamed gingiva-derived mesenchymal stem cells could be effective in terms of osteogenic differentiation, collagen fiber formation, immunoregulation, migration capacity, and testing of dental material and may present a reliable alternative source for healthy gingiva-derived mesenchymal stem cells.